Environmental Local Wisdom Represented in Communication Patterns of Batimbang Tando in Minangkabau’s Culture - Nugra Heni Adnania (EDP Sciences, 2021)
The forms of culture are diverse. One of them is a wedding ceremony. In Minangkabau’s culture, several processes have to be done before the wedding ceremony, and one of them is Batimbang Tando (engagement). This research aims to discuss the communication patterns in the process of Batimbang Tando in Minangkabau’s culture. This research is descriptive qualitative using ethnography of communication approach. The data in this research were obtained from the informants involved in the events. To collect the data, the researchers used non-participant observation by interviewing with note-taking technique. To analyze the data, the researchers used Hymes’s theory of SPEAKING. The result shows that the Batimbang Tando event took place in the boy’s house. In this event, there are several communicative events, such as; Pasambahan, batuka tando, makan bajamba and manantuan ari. In this event, the communication process (pasambahan) uses subtle Minangkabau languages in the form of pantun and talibun. The use of plants like Siriah (betel leaf) and Pinang (areca nut) to symbolize life in Pasambahan indicated that culture and environment could not be separated as they function to preserve harmonious relations between nature and cultural life.